2017
DOI: 10.3390/bs7040074
|View full text |Cite
|
Sign up to set email alerts
|

Financing Cocaine Use in a Homeless Population

Abstract: Background: Cocaine use is highly prevalent among homeless populations, yet little is known about how it is financed. This study examined associations of income sources with cocaine use and financing of drugs in a longitudinal evaluation of a homeless sample. Methods: A homeless sample was recruited systematically in St. Louis in 1999–2001 and longitudinally assessed annually over two years using the Diagnostic Interview Schedule and the Homeless Supplement, with urine drug testing. Results: More than half (55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…Among our sample of PWH, being Black, non-Hispanic/Latinx, having low education attainment, low household income, and recent homelessness or incarceration experiences were significant factors correlated with P12M cocaine use among PWH. These associations are consistent with past research ( John and Wu, 2017 , North and Pollio, 2017 , Zhao et al, 2018 ). A higher prevalence of P12M polysubstance use (including alcohol, marijuana, opioids, heroin, stimulants, and sedatives) was observed among cocaine users than non-users, supporting that polysubstance use is common among cocaine users ( Liu et al, 2019 , Liu et al, 2018 ).…”
Section: Discussionsupporting
confidence: 93%
“…Among our sample of PWH, being Black, non-Hispanic/Latinx, having low education attainment, low household income, and recent homelessness or incarceration experiences were significant factors correlated with P12M cocaine use among PWH. These associations are consistent with past research ( John and Wu, 2017 , North and Pollio, 2017 , Zhao et al, 2018 ). A higher prevalence of P12M polysubstance use (including alcohol, marijuana, opioids, heroin, stimulants, and sedatives) was observed among cocaine users than non-users, supporting that polysubstance use is common among cocaine users ( Liu et al, 2019 , Liu et al, 2018 ).…”
Section: Discussionsupporting
confidence: 93%
“…A recent systematic review found that worse economic status and unemployment has been associated with suicidal behavior [71]. Lack of economic resources seems to increase the burden of the preexisting clinical condition and it is common for users of a highly addictive drug to spend a significant part of their income on acquiring that drug [72][73][74]. This cycle most probably prolongs the burden related to economic vulnerability as long as drug use addictive behavior remains.…”
Section: Plos Onementioning
confidence: 99%
“… a Reported income often appears in dollar values according to data collection year, not publication year. b Conversions to 2020 were done with the U.S. Bureau of Labor Statistics inflation calculator. c Studies that report past 30 days are indicated in table as monthly for time interval (e.g., Conroy, 2001; North & Pollio, 2017). d Income of panhandlers in past month, not necessarily only from panhandling. e Zlotnick and Robertson (1996) report a total, a sample with mental disorders (M.D.…”
Section: Resultsmentioning
confidence: 99%
“… c Studies that report past 30 days are indicated in table as monthly for time interval (e.g., Conroy, 2001; North & Pollio, 2017). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation